Failure modes of postinstalled epoxy anchors in poor concrete, submitted to direct traction tests (Ingenio Magno, 2018)
In our country, the study of failure modes in post-installed anchors has been limited to common concrete resistances, this paper aims to identify the types of failures associated with tested epoxy anchors, and interpret the faults based on existing classifications. The methodology used is based on building post-installed anchors in poor concrete and submitting them to a direct tensile test in the laboratory, analyzing the failure modes presented and determining the possible causes that originate the failure. As a result, any anchor reaches the yield strength of steel or steel failure, the cone failure mode presents the highest load resistance obtained in direct tensile tests. In general, the use of post-installed epoxy anchors with smaller bar diameters is not recommended, the failure modes observed in anchors with small steels are related to low applied load resistances.
Keywords: Adhesion; Epoxy Anchor; Concrete; Post-Installed; Testing; Traction